Extramedullary haematopoeisis causing spinal cord compression - F Ismail; L Huang; Z Lockhat; S Ellemdin; L van der Linde (South African Journal of Radiology, 2010)
Extramedullary haematopoeisis (EMH) is a rare cause of spinal cord compression. However, in a patient with a haematological disorder and in particular thalassaemia, EMH with paraspinal masses should be considered and imaging planned appropriately.